PRESENT CONCEPTS AND FUTURE PERSPECTIVES OF ARTIFICIAL INTELLIGENCE IN PHARMACEUTICAL INDUSTRY. A NARRATIVE REVIEW. - Turki Saleh Almalki*1, Abdulaziz Mohammed Alshuhri2, Saleh Hamood Almaymoni3, Thamer Khoder Almelabi3, Yasser Sufran Alshamrani,3 Mohammed Sufran Alshamrani,4 Hamad Mohammad Almutairi,5 Salamah Almokhalidy,6 Essam Alharshani7, (Chelonian Research Foundation, 2022)
The digitalization of data within the pharmaceutical industry has experienced a significant surge in recent years. However, digitization has resulted in the challenge of collecting, analyzing, and employing such knowledge to handle complex clinical issues. AI is being implemented for this purpose because it can automate the processing of enormous quantities of data. Artificial intelligence [AI] pertains to a technological framework comprising an assortment of advanced instruments and networks that emulate the capabilities of humans. Furthermore, it does not present a significant peril of replacing humans in all circumstances where they are physically present. Artificial intelligence [AI] employs computers and software capable of autonomously analyzing and learning from data in order to determine the most effective course of action for accomplishing objectives. This review elucidates the exponential growth of its applications within the pharmaceutical sector. The extraction of data was conducted in accordance with the Cochrane systematic review methodology standard. A search was conducted across the PubMed, Web of Science, Scopus, and Embase databases for randomized clinical trials [RCTs] and observational studies from 2000 to 2022. Keywords: ‘pharmaceutical’, ‘AI’, ‘machine learning’, ‘Artificial intelligence’.